Infection Control Practices Among Private Practicing Dentists in Nairobi During the Pre-coronavirus Disease 2019 Period - Otieno, Benedict Odhiambo; Kihara, Eunice Njeri; Mua, Bernard Nzioka (Frontiers in Oral Health, 2020)
Background: Background: Cross infection control is a dynamic field which requires frequent updates due to emerging diseases, advancement in technology and scientific knowledge. Despite wide publication of guidelines, a laxity in compliance to the standard precautions of infection control by DHCP has been reported globally. Therefore, there is need to review previous shortcomings in order to adequately secure dental practices during the COVID-19 pandemic. The aim of the study was to determine knowledge and infection control practices by dentists in private practices. The study was done a few months before the first COVID-19 case was confirmed in Kenya. Materials and methods: A descriptive cross-sectional study that was carried out in selected private dental clinics located in Nairobi. Data was collected using an interviewer-administered questionnaire. Convenience sampling method was utilized while data was analyzed using SPSS 20.0.0.0. Results A total of 71 private dentists participated in the study. Their mean age was 38 years with an age range of 27-55 years. Almost all (70,98.6%) the dentist were able to define cross infection correctly. Majority (62,87.3%), correctly differentiated between sterilization and disinfection, while 9(12.7%) had difficulties. Most (68, 95.8%) of the respondents were aware of the Standard Precautions for cross infection control. All participants used face masks and gloves. About half of them (38,54%) practiced hand washing after removal of gloves, 31(43.7%) before and after wearing of gloves, while 2(2.8%) washed hands only before wearing gloves. Only 31(42.3%) and 26(36.6%) participants reported use of rubber dam isolation and impervious barrier respectively. All the dentists reported disposal of sharps into specially labeled containers while about half reported use of disposable suction traps and amalgam separators. Conclusion The dentists had a good knowledge on various aspects of infection control measures that were studied. Use of basic personal protective equipment was widely practiced. There were irregularities in hand hygiene, use of rubber dam, surface barriers and waste management. The work highlights that many dentists were unprepared to manage infectious risk during the COVID-19 outbreak which justified the closure of the dental facilities. Development of strategies to promote adequate and safe practice is highly recommended.